2018
DOI: 10.14419/ijet.v7i4.36.23796
|View full text |Cite
|
Sign up to set email alerts
|

Radioecological Monitoring of Adjacent Territories to the Former Semipalatinsk Nuclear Test Site, East Kazakhstan

Abstract: This paper presents the results of complex radioecological monitoring of the territories, which are situated near the Semipalatinsk Nuclear Test Site, East Kazakhstan region.  The radiometric measurements showed that the concentration of radon and beta particles are below the permissible levels. EROA values of a radon in rooms fluctuates from 44 Bq/m3 to 195 Bq/ m3. The measured values of fluency of betta-particles in all the studied points are less than 10 freq/ min*cm2. A specific activity of radionuclides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…Irrespective of the outcomes described above, the likelihood that meat and meat products exceed the standards for these indicators (MACs) cannot be ignored. Since environmental pollution due to these heavy metals increases every year, and the East Kazakhstan region of the Republic of Kazakhstan was the nuclear testing region for around 42 years, this could lead to the presence of these contaminants in the meat industry eventually ( 46 ). The analysis of toxic substances in the meat and meat products revealed that the average concentration of heavy metals did not exceed the respective MACs.…”
Section: Resultsmentioning
confidence: 99%
“…Irrespective of the outcomes described above, the likelihood that meat and meat products exceed the standards for these indicators (MACs) cannot be ignored. Since environmental pollution due to these heavy metals increases every year, and the East Kazakhstan region of the Republic of Kazakhstan was the nuclear testing region for around 42 years, this could lead to the presence of these contaminants in the meat industry eventually ( 46 ). The analysis of toxic substances in the meat and meat products revealed that the average concentration of heavy metals did not exceed the respective MACs.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed analysis of AA showed a decrease in the AA composition in all samples in comparison with the standards established by WHO/FAO. In the work of Duyssembaev et al (2016) a study of beef from four zones of the test site was also conducted, the following results were obtained: the amount of AA in beef from Sarzhal village (the extreme risk zone) was 87.3%; Akzhar village (the maximum risk zone) was 86.4%; Novopokrovka village (the increased radiation risk zone) was 86.4%; Karatau village (the minimum radiation risk zone) was 84.2%. Thus, this study did not reveal any dependence of the AA content level on the contaminated zone in which the animals were raised.…”
Section: Discussionmentioning
confidence: 99%
“…So, obtaining a safe and complete product is important for the region development (Ospanova, 2017). The territories of the former SNTS have all the conditions for growing high‐quality meat breeds of animals, this is facilitated by the traditions of selective breeding and animal husbandry, large areas of pastures (Duyssembaev et al, 2016). However, the biggest problem, even many decades after the test termination, remains the issue of radiation contamination and its impact on the quality of animal products that can be obtained under these conditions (Kukhtyn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Так, проведен комплексный радиоэкологический мониторинг территорий, расположенных вблизи СИП, где объектами исследования являлись: поч ва, растения и продукты питания местного произ водства. В данных компонентах оценены удельные активности радионуклидов, таких как 241 Am, 137 Cs и 239/240 Pu [8,9]. Также оценены активности 137 Cs в почве, воде, растительности и коровьем молоке в 10 точках трех регионов (Абай, Аягуз и Урджар) которые расположены к юго востоку от СИП [10].…”
unclassified